Microfluidic traction force microscopy to study mechanotransduction in angiogenesis. (July 2017) - Boldock, Luke; Wittkowske, Claudia; Perrault, Cecile M.
Abstract: The formation of new blood vessels from existing vasculature, angiogenesis, is driven by coordinated endothelial cell migration and matrix remodeling in response to local signals. Recently, a growing body of evidence has shown that mechanotransduction, along with chemotransduction, is a major regulator of angiogenesis. Mechanical signals, such as fluid shear stress and substrate mechanics, influence sprouting and network formation, but the mechanisms behind this relationship are still unclear. Here, we present cellular traction forces as possible effectors activated by mechanosensing to mediate matrix remodeling, and encourage the use of TFM to study mechanotransduction in angiogenesis. We also suggest that deciphering the response of EC to mechanical signals could reveal an optimal angiogenic mechanical environment, and provide insight into development, wound healing, the initiation and growth of tumors, and new strategies for tissue engineering.